Treaties and other international agreements on fisheries, oceanographic resources, and wildlife involving the United States (Washington, 1977)
The change in the title from agreements to which the United States is party to agreements involing the United States recognizes the fact that some of the agreements included in this compilation are either not in force or are not in force for the United States.
Keywords: Fishery law and legislation,Luật Thủy sản và pháp luật; United States,Hoa Kỳ